2017
DOI: 10.3329/jninb.v1i2.29842
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Neurodevelopmental Impairments among less than 2 Years Old Children in a Tertiary Care Hospital in Dhaka city

Abstract: Background: Neurodevelopmental impairment is an important issue in the context of normal growth of the children. Objective: The purpose of the present study was to find out the magnitude of neurodevelopmental impairments (NDIs) in young children in a tertiary care hospital Methodology: This cross sectional study was conducted in the Department of Paediatrics at Dhaka Medical College Hospital (DMCH) from January 2010 to June 2010 for a period of six months. All children with the age of 0 to 2 years irrespective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 7 publications
4
1
2
Order By: Relevance
“…In our study, the speech was affected in 40.0%, consistent with Ara et al [10] Other two studies found speech impairment in 26.6% and. 14.5% [2,16].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our study, the speech was affected in 40.0%, consistent with Ara et al [10] Other two studies found speech impairment in 26.6% and. 14.5% [2,16].…”
Section: Discussionsupporting
confidence: 92%
“…Among the high-risk infants on 2 nd assessment, 36.5% of infants, had vision impairment, 30.6% had hearing impairment (Table V). These findings correspond with the study by Ara et al, where vision and hearing impairments were 35.0% and 40.0% respectively [10]. Uddin et al, found vision impairment in 23.5% and hearing impairment in 29.4% [17].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations